Infra-low frequency neurofeedback in application to Tourette syndrome and other tic disorders: A clinical case series - Solberg, Bodil; Solberg, Erlend (Frontiers in Human Neuroscience, 2022)
We describe our clinical experience in treating patients with Tourette syndrome and other tic disorders using Infra-Low Frequency Neurofeedback (ILF NF), often in conjunction with cognitive behavior therapy. Following a narrative description of our approach, we present outcome data for 100 successive cases. Many of the children and adolescents that we have treated since 2005 did not derive sufficient benefit from standard treatment for Tourette syndrome and other tic disorders. In our clinical experience, based on extensive before- and after- testing and symptom tracking, this patient group derived significant additive benefit from complementary neurofeedback treatment. The majority of trainees attained a higher level of functioning and were able to live up to their potential in a way they were not able to prior to neurofeedback treatment.